Implementación de un molino de martillos para el proceso de harina de trigo - Freire Alberto, Lalbay Antonio (2022)
The purpose of the study is the implementation of a hammer mill for flour processing, the purpose is to design this machine for small and medium producers specializing in agricultural activities, providing them with the ease with which they will be able to manipulate the process for grinding since it will not present a level of difficulty to manipulate, eliminating the traditional artisanal flour, high price of food processing and production. The research was carried out to find out how often the wheat mill design was used in the production of flour for consumption, diagnoses and prognoses were made in the description of the problem detailing what needed to be achieved in the project. It was carried out in La Maná canton in the province of Cotopaxi where the results were obtained within a study in which were found all the parameters used to build the machine, performance characteristics, safety factor, materials, and machine speed axis, direction, and limit. It was determined, that the conclusions were reached in the research process.